USE OF PILOTLESS AIRCRAFT IN MODERN WARFARE. ASSESSING THEIR LAWFULNESS UNDER INTERNATIONAL HUMANITARIAN LAW - Peruana de Derecho Internacional, Sociedad (2021)
Despite the advanced technology required for their operation, drones represent another stage inthe human tradition of developing means for waging war remotely. In this sense, they are nodifferent from other advancements and are subject to the same international standards and mustcomply with the same principles as other weapon-platforms. This article focuses on providingan answer on the legality of the use of drones in relation to International Humanitarian Law. Todo so, it briefly addresses the issue of the use of drones in the most common scenario, attacksagainst non-state armed groups in foreign territory, and then concentrates on the compliancewith the principles of international humanitarian law, in order to conclude that theircharacteristics not only allow them to comply with but also may even be regarded as anenhancement in the constant pursuit of enforcing International Humanitarian Law.